Legendre polynomials and its application in solving electric potential due to a sphere - Liew, Siaw Ching; Yudariah Mohammad Yusof; Fakulti Sains (2010)
Project Paper (Sarjana Muda Sains serta Pendidikan (Matematik)) - Universiti Teknologi Malaysia, 2010